Metaverse in business research: a systematic literature review - Egi Arvian Firmansyah; Umar Habibu Umar (Cogent Business & Management, 2023)
This study reviews metaverse literature related to the business discipline. Our first search yielded 323 papers, further filtered based on predefined standards. Accordingly, since our research focuses on the metaverse of business, we limited the Scopus search results by choosing only two categories: business, management, and accounting, as well as economics, econometrics, and finance. Using the PRISMA flowchart, this study reviewed 29 selected documents published by publication outlets in Scopus. The study reveals that most metaverse-business studies employed qualitative methods and were categorized as conceptual papers because the research is in its infancy. Marketing has become the dominant business area since most studies relate metaverse with various marketing activities. Besides, management information and finance come second and third in the number of publications. This result indicates that through metaverse, businesses can attract new customers, retain existing customers, improve firm operations, and streamline business processes. This study's novelty is investigating metaverse studies related to business function areas, which is absent in metaverse literature. One limitation of this study is the single database, namely, Scopus. Further study may employ other databases like Web of Science or Google Scholar. Besides, future studies may explore more metaverse studies concerning more specific topics, such as accounting, auditing, and banking.
Keywords: 650; Business; metaverse; review; SLR; systematic review